Heat-resistant self-repairing ACNTs / fGO-coated TiB2 / ZP / EP anticorrosive paint and preparation method and coating thereof

By adding ACNTs/fGO@TiB2/ZP composite filler to the anti-corrosion coating, the problem of the coating's micropores and cracks being unable to repair themselves was solved, achieving self-repair and improved thermal stability of the coating, thus extending the coating's service life.

CN119264771APending Publication Date: 2025-01-07JILIN POWER SUPPLY COMPANY STATE GRID JILIN ELECTRIC POWER +1

Patent Information

Application Number
CN202411556953.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing anti-corrosion coatings cannot automatically fill and repair micropores and cracks in the coating after damage, allowing corrosive media to penetrate into the coating and affecting its service life.

Method used

ACNTs/fGO@TiB2/ZP composite filler is used. By uniformly dispersing it in epoxy resin, the phosphate loaded on the surface of ACNTs/fGO@TiB2/ZP releases phosphate ions and iron ions during corrosion to form complexes or chelates, which fill the micropores and cracks of the coating. The bonding force is enhanced by the formation of chemical bonds or hydrogen bonds between ACNTs/fGO@TiB2/ZP and the polymer substrate in the coating. At the same time, dicyclohexanone oxaloyl dihydrazone promotes the crosslinking reaction of the coating, and TiB2 improves the thermal stability.

Benefits of technology

It achieves the self-healing function of the coating, enhances the adhesion between the coating and the substrate, improves the corrosion resistance and thermal stability of the coating, and extends the service life of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264771A_ABST
    Figure CN119264771A_ABST
Patent Text Reader

Abstract

The invention provides a heat-resistant self-repairing ACNTs / fGO-coated TiB2 / ZP / EP anticorrosive paint, a preparation method thereof and a coating, relates to the technical field of paints, and aims to solve the problem that the service life of the coating is affected due to the fact that a corrosive medium permeates into the coating because micropores and cracks of the coating cannot be automatically filled and repaired after an existing anticorrosive paint is damaged. The anticorrosive paint is prepared from the following components in parts by mass: 50 to 70 parts of epoxy resin, 0.5 to 1.5 parts of ACNTs / fGO (at) TiB2 / ZP filler, 0.1 to 0.25 part of 3-amino-1H-1, 2, 4-triazole (ATA), 3 to 6 parts of solvent, 0.1 to 1 part of dicyclohexanone oxalyl dihydrazone, 20 to 25 parts of curing agent and 0.01 to 0.1 part of auxiliary agent, and the ratio of the body filler to the ACNTs / fGO (at) TiB2 / ZP filler is (0.01 to 0.1) to 1. The invention also provides a preparation method of the heat-resistant self-repairing ACNTs / fGO-coated TiB2 / ZP / EP anticorrosive paint and a heat-resistant self-repairing anticorrosive coating. The method is used for relieving chemical corrosion of metal equipment and metal pipelines.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating and a preparation method and coating thereof. Background Art

[0002] Metals react chemically with air, water, soil and other media, and the surface is gradually destroyed and deteriorated, which not only reduces the strength and durability of the metal, but also leads to structural failure and safety accidents. In order to slow down metal corrosion, common protective measures include coating, plating, anodic protection and other methods to isolate the metal from the contact with the corrosive medium. Among them, coating the metal surface with an anti-corrosion coating is simple to operate and low in cost, and is currently a commonly used anti-corrosion measure. However, the commonly used epoxy resin coating is affected by environmental factors or its own structure, and some tiny micropores and cracks are inevitable on the surface of the coating. The corrosive medium penetrates the coating, and it is difficult to completely prevent the occurrence of metal corrosion. Adding two-dimensional nanosheets GO to epoxy resin can reduce the micropores and cracks of the coating, but GO has a large specific surface area and is easy to agglomerate in epoxy resin, reducing the stability of the coating. At the same time, the coating on the metal surface is exposed to air or soil for a long time, the adhesion of the coating decreases, and it is easy to peel off from the metal surface, thereby reducing the protective life of the coating.

[0003] In industrial fields, such as the oil, gas and chemical industries, many metal equipment and metal pipelines are exposed to high temperature environments. Anticorrosive coatings with good thermal stability can resist physical and chemical changes caused by high temperatures, such as softening, melting or degradation, prevent cracking, peeling or blistering, and reduce the occurrence of safety accidents such as fires, but epoxy resin coatings have poor heat resistance and are prone to aging. At present, GO is mainly surface modified or modified GO composites are prepared using organic solvents to improve its dispersibility and adhesion in epoxy resin. However, the use of organic solvents to prepare GO does not meet environmental protection requirements. In addition, some modifiers (such as octylamine, dodecylamine, aminosilane, etc.) cannot effectively disperse GO in epoxy resin. These modifiers can only be modified using the epoxy groups in GO, and the grafting amount is limited by the epoxy content. In addition, directly adding surface-modified GO to the epoxy resin matrix cannot effectively improve the thermal stability of the coating. Therefore, the existing technology needs to be further improved and improved, and it is necessary to develop a new anticorrosive coating that meets environmental protection requirements and has heat-resistant self-repairing functions. Summary of the invention

[0004] The technical problems to be solved by the present invention are:

[0005] Existing anti-corrosion coatings are unable to automatically fill and repair the micropores and cracks in the coating after being damaged, causing corrosive media to penetrate into the coating, affecting the service life of the coating.

[0006] The present invention adopts the following technical solutions to solve the above technical problems:

[0007] The present invention provides a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating, which comprises, by mass, 50 to 70 parts of epoxy resin, 0.5 to 1.5 parts of ACNTs / fGO@TiB2 / ZP filler, 0.1 to 0.25 parts of 3-amino-1H-1,2,4-triazole (ATA), 3 to 6 parts of solvent, 0.1 to 1 part of dicyclohexanone oxalyldihydrazone, 20 to 25 parts of curing agent and 0.01 to 0.1 part of auxiliary agent, and the ratio of the physical filler to the ACNTs / fGO@TiB2 / ZP filler is 0.01 to 0.1:1.

[0008] Furthermore, the epoxy resin is at least one of E-15, E-42, E-44, E-51 or E-54 epoxy resins.

[0009] Furthermore, the curing agent is at least one of W93, 593, 650, 651 or T31 type curing agents.

[0010] Furthermore, the auxiliary agent is at least one of a defoaming agent, a wetting agent or a dispersant.

[0011] Furthermore, the physical filler is at least one of talcum powder, mica powder or bentonite.

[0012] Furthermore, the solvent consists of N-methylpyrrolidone, n-butanol and microcrystalline cellulose.

[0013] The invention provides a method for preparing a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating. The preparation method comprises the following steps: adding a curing agent and an auxiliary agent to a solvent according to parts by mass, stirring evenly to obtain a mixture system one, adding an epoxy resin to the mixture system one to obtain a mixture system two, adding an ACNTs / fGO@TiB2 / ZP filler, ATA, dicyclohexanone oxalyldihydrazone and a body filler to the mixture system two, mixing evenly to obtain an ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating;

[0014] The preparation method of the ACNTs / fGO@TiB2 / ZP filler is as follows: functionalized graphene oxide (fGO), functionalized carbon nanotubes ACNTs and TiB2 are added to deionized water according to mass fractions and mixed evenly, zinc phosphate is added, and the mixture is stirred at 30°C to 40°C under nitrogen for 2 to 3 hours to obtain a mixed solution, and the mixed solution is transferred to a reactor to react for 8 to 12 hours to obtain the ACNTs / fGO@TiB2 / ZP filler;

[0015] The preparation method of the functionalized graphene oxide (fGO) is as follows: GO powder, cetylpyridinium chloride, chitosan and KH-550 are added to DMF according to mass fractions, mixed and reacted for 1 to 3 hours, centrifuged, washed, and dried to obtain the functionalized graphene oxide (fGO);

[0016] The preparation method of the functionalized carbon nanotubes ACNTs is as follows: CNTs and CTAB powders are added into deionized water according to mass fractions, stirred for 1 to 3 hours, and centrifuged to dry to obtain the functionalized carbon nanotubes ACNTs powders.

[0017] Furthermore, in the preparation method of ACNTs / fGO@TiB2 / ZP filler, the mass ratio of functionalized graphene oxide (fGO), functionalized carbon nanotubes ACNTs, TiB2 and zinc phosphate is: (1.8-2.5): (1.3-1.5): (1.2-1.5): (1.2-2).

[0018] Furthermore, in the preparation method of functionalized graphene oxide (fGO), the mass ratio of GO powder, cetylpyridinium chloride, chitosan and KH-550 is: (1.2-2): (2-3): (0.6-0.8): (2-3).

[0019] The present invention provides a heat-resistant self-repairing anti-corrosion coating, wherein the anti-corrosion coating is formed by the anti-corrosion coating described in the above technical solution.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The present invention adds a small amount of uniformly dispersed ACNTs / fGO@TiB2 / ZP composite filler to the anti-corrosion coating, which can effectively avoid the natural agglomeration of GO. When the phosphate loaded on the surface of ACNTs / fGO@TiB2 / ZP is corroded, it can release phosphate ions and react with iron ions to form complexes or chelates, fill the micropores and cracks of the coating, and achieve automatic repair after damage. Second, ACNTs / fGO@TiB2 / ZP composite fillers have a large number of oxygen-containing functional groups, such as hydroxyl, carboxyl and epoxy groups, which can form chemical bonds or hydrogen bonds with the polymer substrate in the coating, thereby enhancing the bonding force between the coating and the substrate; it has good chemical stability, can improve the coating's resistance to chemical substances, and reduce the coating shedding caused by chemical corrosion. 3. ACNTs / fGO@TiB2 / ZP composite filler has a high aspect ratio and large surface area, which can form a physical barrier in the epoxy resin, slow down the penetration of corrosive media, and thus improve the corrosion resistance of the coating; at the same time, dicyclohexanone oxalyl dihydrazone can promote the cross-linking reaction of the coating and improve the mechanical properties. TiB2 has high thermal conductivity and chemical stability, good thermal shock resistance, and can maintain structural stability in an environment with rapid temperature changes, forming a stable chemical environment in the coating and reducing the damage to the epoxy resin coating.

[0022] The anti-corrosion coating of the invention is green and environmentally friendly, has a simple preparation process, stable performance and a long service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope image of ACNTs / fGO@TiB2 / ZP in an embodiment of the present invention;

[0024] Figure 2 This is the intuitive morphology of the ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating in the embodiment of the present invention;

[0025] Figure 3 This is a thermogravimetric graph of the ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating in an embodiment of the present invention;

[0026] Figure 4 This is the Nyquist diagram of the anti-corrosion coating in an embodiment of the present invention immersed in a 3.5wt% NaCl solution for 30 days;

[0027] Figure 5 The following are photos of the acid and alkali resistance test of the anti-corrosion coating in the embodiment of the present invention. DETAILED DESCRIPTION

[0028] In order to enable those skilled in the art to better understand the scheme of the present invention, exemplary implementations or embodiments of the present invention will be described below in conjunction with the accompanying drawings. Obviously, the described implementations or embodiments are only implementations or embodiments of a part of the present invention, not all of them. Based on the implementations or embodiments of the present invention, all other implementations or embodiments obtained by ordinary technicians in the field without creative work should fall within the scope of protection of the present invention.

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0030] Example 1

[0031] A method for preparing a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating comprises the following steps:

[0032] Add 90mL of concentrated sulfuric acid and 10mL of concentrated phosphoric acid to a three-necked flask, add 2g of flake graphite, and then add an appropriate amount of KMnO4, and react in a water bath at 50℃ for 2h. Slowly add 200mL of deionized water and react at 95℃ for 15min. After the reaction is completed, add 30mL of H2O2 and react for 15min. Centrifuge, wash with dilute hydrochloric acid, anhydrous ethanol, and deionized water in turn, remove the supernatant, repeat the washing several times until the pH of the supernatant is ≥6, dry and grind the precipitate to obtain GO powder.

[0033] 0.5 g GO powder, 1.5 g cetylpyridinium chloride, 0.25 g chitosan and 1 mL KH-550 were added to 20 mL DMF, stirred continuously at 60 °C for 1 h, centrifuged, washed and dried to obtain functionalized graphene oxide (fGO).

[0034] 0.8 g of CNTs was added into 20 mL of deionized water, and 1 g of CTAB powder was added, and the mixture was stirred and mixed continuously for 1 h, and then centrifuged and dried to obtain ACNTs powder.

[0035] 1 g fGO, 0.5 g ACNTs and 1 g TiB2 were added to a three-necked flask containing 20 mL deionized water, and magnetic stirring was performed. 0.75 g zinc phosphate was added. The mixture was stirred for 2 h at 30 ° C under nitrogen to obtain a mixed solution. The mixed solution was transferred to a reactor and reacted at 100 ° C for 8 h. Centrifugation, washing, and freeze-drying were performed to obtain the following: Figure 1 ACNTs / fGO@TiB2 / ZP filler shown.

[0036] 1.5 mL of N-methylpyrrolidone, 1 mL of n-butanol and 0.5 g of microcrystalline cellulose were added to a beaker and stirred for 30 min to obtain a mixed solvent; 20 g of curing agent and additives: 0.01 g of defoaming agent, 0.01 g of dispersant, and 0.01 g of wetting agent were added to the mixed solvent and stirred evenly to obtain a mixture system 1; 50 g of epoxy resin was added to the mixture system 1 to obtain a mixture system 2, and 0.5 g of ACNTs / fGO@TiB2 / ZP filler, 0.1 of 3-amino-1H-1,2,4-triazole (ATA), 0.1 g of dicyclohexanone oxalyldihydrazone and physical fillers: 0.0075 g of talc, 0.015 g of mica powder and 0.0075 g of bentonite were added to the mixture system 2, and stirred evenly to obtain a heat-resistant self-healing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0037] Example 2

[0038] (1) ACNTs / fGO@TiB2 / ZP filler was prepared by the method of Example 1.

[0039] (2) Add 3.5 mL of N-methylpyrrolidone, 1.5 mL of n-butanol and 0.75 g of microcrystalline cellulose into a beaker and stir for 30 min to obtain a mixed solvent; then add 23 g of curing agent and additives: 0.012 g of defoaming agent, 0.012 g of dispersant, and 0.012 g of wetting agent to the mixed solvent in sequence and stir evenly to obtain a mixture system 1; add 55 g of epoxy resin to the mixture system 1 to obtain a mixture system 2, add 1 g of ACNTs / fGO@TiB2 / ZP filler, 0.175 g of ATA, 0.35 g of dicyclohexanone oxalyldihydrazone and physical fillers: 0.035 g of talc, 0.025 g of mica powder and 0.025 g of bentonite to the mixture system 2, stir evenly to obtain a heat-resistant self-healing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0040] Example 3

[0041] (1) ACNTs / fGO@TiB2 / ZP filler was prepared by the method of Example 1.

[0042] (2) Add 3.2 mL of N-methylpyrrolidone, 1.6 mL of n-butanol and 1.2 g of microcrystalline cellulose into a beaker and stir for 30 min to obtain a mixed solvent; then add 23 g of curing agent and additives: 0.02 g of defoaming agent, 0.02 g of dispersant, and 0.02 g of wetting agent to the mixed solvent in sequence and stir evenly to obtain a mixture system 1; add 60 g of epoxy resin to the mixture system 1 to obtain a mixture system 2, add 1.5 g of ACNTs / fGO@TiB2 / ZP filler, 0.2 g of ATA, 0.5 g of dicyclohexanone oxalyldihydrazone and physical fillers: 0.05 g of talc, 0.004 g of mica powder and 0.004 g of bentonite to the mixture system 2, stir evenly to prepare a heat-resistant self-healing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0043] Example 4

[0044] (1) ACNTs / fGO@TiB2 / ZP filler was prepared by the method of Example 1.

[0045] (2) Add 2 mL of N-methylpyrrolidone, 1.2 mL of n-butanol and 0.9 g of microcrystalline cellulose into a beaker and stir for 30 min to obtain a mixed solvent; then add 23 g of curing agent and additives: 0.03 g of defoaming agent, 0.03 g of dispersant, and 0.03 g of wetting agent to the mixed solvent in sequence and stir evenly to obtain a mixture system 1; add 65 g of epoxy resin to the mixture system 1 to obtain a mixture system 2, add 0.6 g of ACNTs / fGO@TiB2 / ZP filler, 0.25 g of ATA, 1 g of dicyclohexanone oxalyldihydrazone and physical fillers: 0.02 g of talc, 0.015 g of mica powder and 0.015 g of bentonite to the mixture system 2, stir evenly to obtain a heat-resistant self-healing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0046] Example 5

[0047] (1) ACNTs / fGO@TiB2 / ZP filler was prepared by the method of Example 1.

[0048] (2) Add 2.4 mL of N-methylpyrrolidone, 1.5 mL of n-butanol and 1 g of microcrystalline cellulose into a beaker and stir for 30 min to obtain a mixed solvent; then add 25 g of curing agent and additives: 0.03 g of defoaming agent, 0.03 g of dispersant, and 0.03 g of wetting agent to the mixed solvent in sequence and stir evenly to obtain a mixture system 1; add 70 g of epoxy resin to the mixture system 1 to obtain a mixture system 2, add 1 g of ACNTs / fGO@TiB2 / ZP filler, 0.225 g of ATA, 0.8 g of dicyclohexanone oxalyldihydrazone and physical fillers: 0.03 g of talc, 0.035 g of mica powder and 0.035 g of bentonite to the mixture system 2, stir evenly to obtain a heat-resistant self-healing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0049] Example 6

[0050] A method for preparing a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating comprises the following steps:

[0051] GO powder was prepared by the method of Example 1.

[0052] 1.2 g GO powder, 2 g cetylpyridinium chloride, 0.6 g chitosan and 2.5 mL KH-550 were added to 20 mL DMF, stirred continuously at 60 °C for 2 h, centrifuged, washed and dried to obtain functionalized graphene oxide (fGO).

[0053] 1.3 g of CNTs was dissolved in 20 mL of deionized water, and 1.55 g of CTAB powder was added. After continuous stirring for 3 h, the mixture was centrifuged and dried to obtain ACNTs powder.

[0054] 1.85 g fGO, 1.3 g ACNTs and 1.2 g TiB2 were added to a three-necked flask containing 20 mL deionized water, and 1.25 g zinc phosphate was added under magnetic stirring. After stirring for 2 h under nitrogen at 35 °C, the mixture was transferred to a reactor and reacted at high temperature for 10 h. After centrifugation, washing and freeze-drying, ACNTs / fGO@TiB2 / ZP filler was obtained.

[0055] The method of Example 5 was used to prepare a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0056] Example 7

[0057] A method for preparing a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating comprises the following steps:

[0058] GO powder was prepared by the method of Example 1.

[0059] 1.5 g GO powder, 2.25 g cetylpyridinium chloride, 0.65 g chitosan and 3 mL KH-550 were added to 20 mL DMF, stirred continuously at 60 °C for 2 h, centrifuged, washed and dried to obtain functionalized graphene oxide (fGO).

[0060] 1.35 g of CNTs was dissolved in 20 mL of deionized water, and 1.75 g of CTAB powder was added. The mixture was stirred for 3 h and centrifuged to obtain ACNTs powder.

[0061] 2g fGO, 1.3g ACNTs and 1.35g TiB2 were added to a three-necked flask containing 20mL deionized water, and 1.45g zinc phosphate was added under magnetic stirring; the mixture was stirred for 3h under nitrogen at 40℃ to obtain a mixed solution; the mixed solution was transferred to a reactor and reacted at high temperature for 10h; centrifuged, washed, and freeze-dried to obtain ACNTs / fGO@TiB2 / ZP filler.

[0062] The method of Example 5 was used to prepare a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0063] Example 8

[0064] A method for preparing a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating comprises the following steps:

[0065] GO powder was prepared by the method of Example 1.

[0066] 1.75 g GO powder, 2.5 g cetylpyridinium chloride, 0.7 g chitosan and 3 mL KH-550 were added to 20 mL DMF, stirred continuously at 60 °C for 2.5 h, centrifuged, washed and dried to obtain functionalized graphene oxide (fGO).

[0067] 1.45 g of CNTs was dissolved in 20 mL of deionized water, and 2 g of CTAB powder was added. After continuous stirring for 3 h, the mixture was centrifuged and dried to obtain ACNTs powder.

[0068] 2.25 g fGO, 1.4 g ACNTs and 1.35 g TiB2 were added to a three-necked flask containing 20 mL deionized water, and 1.75 g zinc phosphate was added under magnetic stirring; the mixture was stirred for 3 h under nitrogen at 40 °C to obtain a mixed solution; the mixed solution was transferred to a reactor and reacted at high temperature for 11 h; centrifuged, washed, and freeze-dried to obtain ACNTs / fGO@TiB2 / ZP filler.

[0069] The method of Example 5 was used to prepare a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0070] Example 9

[0071] A method for preparing a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating comprises the following steps:

[0072] GO powder was prepared by the method of Example 1.

[0073] 2 g GO powder, 3 g cetylpyridinium chloride, 0.75 g chitosan and 3 mL KH-550 were added to 20 mL DMF, stirred at 60 °C for 3 h, centrifuged, washed and dried to obtain functionalized graphene oxide (fGO).

[0074] 1.5 g of CNTs was dissolved in 20 mL of deionized water, and 2.4 g of CTAB powder was added. After continuous stirring for 3 h, the mixture was centrifuged and dried to obtain ACNTs powder.

[0075] 2.5 g fGO, 1.5 g ACNTs and 1.5 g TiB2 were added into a three-necked flask containing 20 mL deionized water, and 2 g zinc phosphate was added under magnetic stirring. After stirring for 3 h under nitrogen at 40 °C, the mixture was transferred to a reactor and reacted at high temperature for 12 h. After centrifugation, washing and freeze-drying, ACNTs / fGO@TiB2 / ZP filler was obtained.

[0076] The method of Example 5 was used to prepare a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating.

[0077] Comparative Example 1: In this comparative example, no ACNTs / fGO@TiB2 / ZP filler is added to the coating, and the EP anti-corrosion coating is prepared by the method of Example 5.

[0078] The performance test of the anticorrosive coatings prepared in Examples 1 to 9 and Comparative Example 1 is as follows: the surface of the mild steel is polished, the surface oil is removed with anhydrous ethanol, and the mild steel is dried in an oven. The prepared heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosive coating is evenly applied to the mild steel surface with an applicator, left at room temperature for 48 hours, and then dried in an oven at 40°C for 3 to 5 hours to obtain a metal coating sample. Figure 2 Shown is the ACNTs / fGO@TiB2 / ZP anti-corrosion coating of Example 5.

[0079] The prepared coating samples were subjected to thermogravimetric testing in a nitrogen atmosphere at a heating rate of 10°C / min to study the thermal stability of the coating. The results are shown in Table 1. Figure 3Shown is a comparison of the thermogravimetric curves of the ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating prepared by the coating of Example 5 and the coating prepared by the coating of Comparative Example 1. It can be seen that the initial decomposition temperature of the ACNTs / fGO@TiB2 / ZP / EP anti-corrosion coating is 36.5°C higher than that of the coating of Comparative Example 1, indicating that the addition of ACNTs / fGO@TiB2 / ZP filler enhances the thermal stability of the coating.

[0080] The prepared metal specimens were placed in 3.5wt% NaCl solution for electrochemical impedance spectroscopy. The electrochemical workstation used a three-electrode system, with graphite as the auxiliary electrode, a saturated Ag / AgCl electrode as the reference electrode, and low-carbon steel coated with the coating as the working electrode. The test conditions were room temperature. Figure 4 The Nyquist plot of the ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating prepared by the coating of Example 5 after immersion in a 3.5wt% NaCl aqueous solution for 30 days is shown. The results show that after immersion for 20 days, the impedance arc radius of the coating is slightly larger than that after immersion for 10 days. The results show that the corrosion inhibitor released from the coating forms a protective film with the metal substrate, which makes the coating have a certain self-healing effect. However, after immersion for 30 days, the impedance arc radius of the coating is still large, and the impedance modulus can reach 10 9 It is of the order of magnitude, indicating that it has super high corrosion resistance.

[0081] The prepared coatings were tested for hardness according to GB / T 6739-2022 "Determination of film hardness by pencil method for paints and varnishes", coating adhesion according to GB / T 9286-2021 "Paint and varnish scratch test", coating flexibility according to GB / T 1731-2020 "Determination of flexibility of paint and putty film", and coating impact resistance according to GB / T 1732-2020 "Determination of impact resistance of paint film". The results are shown in Table 1, indicating that the anti-corrosion coating with the addition of ACNTs / fGO@TiB2 / ZP can significantly improve its mechanical properties.

[0082] The acid and alkali resistance of the coating is analyzed according to GB / T 9274-1988 "Determination of resistance of paints and varnishes to liquid media". Figure 5 The figure shows the comparison of the acid and alkali resistance test results of the anticorrosive coating prepared by the coating of Example 5 and Comparative Example 1. It can be seen that after the coating of Comparative Example 1 was immersed in the acid and alkali solution for 7 days, the surface showed obvious blistering and discoloration; however, the coating of Example 5 did not change significantly during the test, indicating that it has good acid and alkali resistance.

[0083] Table 1

[0084]

[0085]

[0086] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art may make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating, characterized in that: The anti-corrosion coating comprises, by mass, 50 to 70 parts of epoxy resin, 0.5 to 1.5 parts of ACNTs / fGO@TiB2 / ZP filler, 0.1 to 0.25 parts of 3-amino-1H-1,2,4-triazole, 3 to 6 parts of solvent, 0.1 to 1 part of dicyclohexanone oxalyldihydrazone, 20 to 25 parts of curing agent and 0.01 to 0.1 parts of auxiliary agent, and the ratio of the physical filler to the ACNTs / fGO@TiB2 / ZP filler is 0.01 to 0.1:

1.

2. The heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating according to claim 1, characterized in that: The epoxy resin is at least one of E-15, E-42, E-44, E-51 or E-54 epoxy resins.

3. The heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating according to claim 1, characterized in that: The curing agent is at least one of W93, 593, 650, 651 or T31 type curing agents.

4. The heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating according to claim 1, characterized in that: The auxiliary agent is at least one of a defoamer, a wetting agent or a dispersant.

5. The heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating according to claim 1, characterized in that: The physical filler is at least one of talcum powder, mica powder or bentonite.

6. The heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating according to claim 1, characterized in that: The solvent consists of N-methylpyrrolidone, n-butanol and microcrystalline cellulose.

7. A method for preparing a heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating, characterized in that: The preparation method comprises: adding a curing agent and an auxiliary agent to a solvent according to the mass fraction, stirring evenly to obtain a mixture system 1, adding an epoxy resin to the mixture system 1 to obtain a mixture system 2, adding ACNTs / fGO@TiB2 / ZP filler, 3-amino-1H-1,2,4-triazole, dicyclohexanone oxalyl dihydrazone and a body filler to the mixture system 2, mixing evenly to obtain an ACNTs / fGO@TiB2 / ZP / EP anticorrosive coating; The preparation method of the ACNTs / fGO@TiB2 / ZP filler is as follows: functionalized graphene oxide, functionalized carbon nanotubes ACNTs and TiB2 are added to deionized water according to mass fractions and mixed evenly, zinc phosphate is added, and the mixture is stirred at 30°C to 40°C under nitrogen for 2 to 3 hours to obtain a mixed solution, and the mixed solution is transferred to a reactor to react for 8 to 12 hours to obtain the ACNTs / fGO@TiB2 / ZP filler; The preparation method of the functionalized graphene oxide is as follows: GO powder, cetylpyridinium chloride, chitosan and KH-550 are added to DMF according to mass fractions, mixed and reacted for 1 to 3 hours, centrifuged, washed, and dried to obtain the functionalized graphene oxide; The preparation method of the functionalized carbon nanotubes ACNTs is as follows: CNTs and CTAB powders are added into deionized water according to mass fractions, stirred for 1 to 3 hours, and centrifuged to dry to obtain the functionalized carbon nanotubes ACNTs powders.

8. The method for preparing the heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating according to claim 7, characterized in that: In the preparation method of ACNTs / fGO@TiB2 / ZP filler, the mass ratio of functionalized graphene oxide, functionalized carbon nanotubes ACNTs, TiB2 and zinc phosphate is: (1.8-2.5): (1.3-1.5): (1.2-1.5): (1.2-2).

9. The method for preparing the heat-resistant self-repairing ACNTs / fGO@TiB2 / ZP / EP anticorrosion coating according to claim 8, characterized in that: In the preparation method of functionalized graphene oxide, the mass ratio of GO powder, cetylpyridinium chloride, chitosan and KH-550 is: (1.2-2): (2-3): (0.6-0.8): (2-3).

10. A heat-resistant self-repairing anti-corrosion coating, characterized in that: The anti-corrosion coating is formed by the anti-corrosion coating according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Electrically-conducting paint based on TiB2 and its preparation method and application

    CN101148549A

  • Electrically conductive anti-corrosive coating and preparation method thereof

    CN108948949A

  • Preparation method of graphene oxide modified composite coating

    CN112552788A

  • Heavy anti-corrosion coating with self-healing function and preparation and use method thereof

    CN112920689A

  • Nano composite material EP (at) DA (at) GO (at) M, preparation method of nano composite material, waterborne epoxy heavy anti-corrosion coating with slow release function and preparation method of waterborne epoxy heavy anti-corrosion coating

    CN118755347A

Cited By

  • Preparation method of noise-reducing and anti-corrosion multifunctional coating

    CN120157950A